Performance study of a DS/CDMA-based LEO satellite system - Lim, M. L. (2008)
The potential of Direct Sequence Code-Division Multiple Access (DS/CDMA) as the Third-Generation (3-G) wireless access technology candidate has motivated this project. In this thesis, a simple equatorial LEO satellite constellation was first constructed. A wideband satellite fading channel model proposed by Glisic et. al. was used as the platform to the subsequent works.